Penggandaan Skala Produksi Bioinsektisida Bacillus thuringiensis var. israelensis untuk Membasmi Jentik Nyamuk Aedes aegypti - Mulyorini Rahayuningsih; Khaswar Syamsu; Abdul Aziz Darwis; Rini Purnawati (Jurnal Ilmu Pertanian Indonesia, 2007)
The objective of this research is to study the scaling up of bionsecticide production from Bacillus thuringiensisvar. israelensisusing onggok (a cassava by-product) as a carbon source. The insecticide produced was used to eradicate Aedes aegypti larvae. The product was a crystal protein produced during bacterial sporulation. Scaling up from laboratory to pilot plant scale was done using two methods, i.e. constant agitation power per unit volume (Pg/V) and constant oxygen transfer coefficient (kLa). The results showed that yield of product per substrate (Yp/s) of Pg/V based product with the value of 3.52 ± 0.02 spora per gram substrates was higher than Yp/s of  kLa based product with the value of 2.96 spora per gram substrate.  Logarithmic value of viable spore count (log of VSC) was also higher, i.e. 7.23 ± 0.30 for Pg/V based product as compared to 7.17 ± 0.20 for kLa based product. Substrate efficiency was also higher in Pg/V based (92.47%) than kLa based (64.87%). LC50 of Pg/V based product was lower (0.49 μg/ml) meaning that it was more toxic than kLa based product (0.62 μg/ml). Amino acid content of Pg/V based product was also higher than kLa based product. Constant Pg/V method was suggested as a based on the scaling up of bioinsecticide production of B. thuringiensis israe/ensison industrial scale. Keywords: bioinsecticide, Bacillus thuringiensisvar. israelensis, kLa, Pg/V, LC50, viable spore count